Attributable risk of Alzheimer's dementia attributed to age‐related neuropathologies. Issue 1 (19th December 2018) - Boyle, Patricia A.; Yu, Lei; Leurgans, Sue E.; Wilson, Robert S.; Brookmeyer, Ron; Schneider, Julie A.; Bennett, David A.
Abstract : Objective: The degree to which Alzheimer's versus other neuropathologies contribute to the risk of Alzheimer's dementia is unknown. We examined the risk of Alzheimer's dementia attributable to pathologic AD and 8 other neuropathologies. Methods: Participants (n = 1, 161) came from 2 clinical‐pathological studies of aging. Multivariable logistic regression models examined associations of 8 neuropathological indices with Alzheimer's dementia and quantified the percentage of cases attributable to each. Furthermore, because some dementia cases are not driven by common neuropathologies, we re‐estimated the attributable risks after empirically adjusting for such cases. Results: Of 1, 161 persons, 512 (44.1%) had Alzheimer's dementia at time of death. With the exception of microinfarcts, all neuropathological indices were independently associated with greater odds of Alzheimer's dementia. Two hundred ten (41.0%) Alzheimer's dementia cases were attributable to pathological AD. Separately, 8.9% were attributable to macroscopic infarcts, 10.8% to Lewy bodies, 5.2% to hippocampal sclerosis, 11.7% to transactive response DNA‐binding protein 43, 8.1% to cerebral amyloid angiopathy, 6.0% to atherosclerosis, and 5.2% to arteriolosclerosis. A total of 83.3% of cases were attributable to all 8 indices combined. However, after further adjustment for cases driven by other factors, a total of 67.5% of cases were attributable to all 8 neuropathologic indices combined. Interpretation: Pathological AD accounts for a considerable percentage of Alzheimer's dementia cases, but multiple other neuropathologies also contribute. In total, just over two‐thirds of Alzheimer's dementia cases are attributable to common age‐related neuropathologies, suggesting that other disease and resilience factors are important.ANN NEUROL 2019;85:114–124.